Surface properties and color stability of an acrylic resin combined with an antimicrobial polymer - Pero, Ana Carolina [UNESP]; Ignárcio, Jaqueline [UNESP]; Giro, Gabriela [UNESP]; Mendoza-marin, Danny Omar [UNESP]; Paleari, André Gustavo [UNESP]; Compagnoni, Marco Antonio [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
INTRODUCTION: The occurrence of stomatitis is common since the surface characteristics of the dentures may act as reservoirs for microorganisms and have the potential to support biofilm formation. PURPOSE: To assess the surface properties (wettability/roughness) and color stability of an acrylic resin combined with the antimicrobial polymer poly (2-tert-butylaminoethyl) methacrylate (PTBAEMA). MATERIAL AND METHOD: Thirty disc-shaped specimens of an acrylic resin (Lucitone 550) were divided into three groups: 0% (control); 5% and 10% PTBAEMA. Surface roughness values (Ra) were measured using a profilometer and wettability was determined through contact angle measurements using a goniometer and deionized water as a test liquid. Color data were measured with a spectrophotometer. Kruskal-Wallis and Dunn's test were used to compare roughness values. Wettability data were analyzed using ANOVA and Tukey's test. Color data were compared using the Student's t-test and ∆E values were classified according to the National Bureau of Standards (NBS). All statistical analyses were performed considering α=.05. RESULT: Significant differences (p<.05) were detected among the groups for roughness, wettability and color stability. According to the NBS, the color changes obtained in the 5% and 10% PTBAEMA groups were appreciable and much appreciable, respectively. CONCLUSION: It could be concluded that PTBAEMA incorporation in an acrylic resin increased the roughness and wettability of surfaces and produced color changes with clinical relevance.

INTRODUÇÃO: A ocorrência de estomatite protética é relativamente comum uma vez que as superfícies das próteses bucais representam um ambiente propício para adesão de microrganismos orais e formação de biofilme. OBJETIVO: Avaliar as propriedades de superfície (molhabilidade/rugosidade) e estabilidade de cor de uma resina acrílica combinada com o polímero antimicrobiano poli (2-tert-butilaminoetil) metacrilato (PTBAEMA). MATERIAL E MÉTODO: Trinta espécimes em formato de disco de uma resina acrílica (Lucitone 550) foram divididos em três grupos: 0% (controle), 5% e 10% PTBAEMA. Os valores de rugosidade (Ra) foram medidos utilizando um rugosímetro, e a molhabilidade foi determinada através de medições de ângulo de contato utilizando um goniômetro e água deionizada como líquido teste. Dados de cores foram medidos com um espectrofotômetro. Os testes de Kruskal-Wallis e Dunn foram utilizados para comparar os valores de rugosidade. Os dados de molhabilidade foram analisados utilizando-se ANOVA e teste de Tukey. Os dados de cor foram comparados com o teste t de Student e valores ΔE foram classificados de acordo com o National Bureau of Standards (NBS). Todas as análises estatísticas foram realizadas considerando α = 0,05. RESULTADO: Diferenças significativas (p<0,05) foram detectadas entre os grupos para rugosidade, molhabilidade, e estabilidade de cor. De acordo com o NBS, as alterações de cor obtidas nos grupos 5% e 10% PTBAEMA foram marcante e extremamente marcante, respectivamente. CONCLUSÃO: Pode-se concluir que a incorporação de PTBAEMA em uma resina acrílica aumentou a rugosidade e molhabilidade das superfícies e produziu alterações de cor com relevância clínica.
Propriedades de superfície e estabilidade de cor de uma resina acrílica combinada com um polímero antimicrobiano
Keywords: Acrylic resins; products with antimicrobial action; wettability; color; physical properties; Resinas acrílicas; produtos com ação antimicrobiana; molhabilidade; cor; propriedades físicas